Strengthening Agricultural Investment through Sustainable Islamic Banking - Purbawati Setyaningsih; Acep R Jayaprawira (International Journal of Business Studies, 2020)
This study analyzes how agricultural investments may strengthen the Islamic banking industry that is sustainable in the short and long term. Qualitative data sources are secondary data from BPS, Baznas, ACT Global Waqf and research on BWI in the form of secondary data from March 2007 to December 2018. Data were analyzed using the Error Correction Model (ECM) Methodology. Ziswaf have a signiicnt effect on GDP both of the long term and the short term, with the ECT coeficient was - 1.81E-07 meaning that there are increasing GDP will be adjusted within one (1) year with the residual speed of the balance value of - 181 percent. In the long term, the GDP have inluented simultaneously by all independent variables with affected positively by Exports-Agi, PMDN and Ziswaf signiicantly; and it have inluenced negatively by Export signiicantly at the R-square level of 0.98 meaning that the variables are tested to provide almost all the information needed to predict the GDP. Export-Agi was the most inluence with a value of coeficient variable 44.875570. While in the short term, GDP was signiicantly inluenced by Ziswaf on R-square 0.26 which means that there have 74 per cent of other variables outside the model that affect GDP. The selection of competitive plants in the zakat distribution program and the use of idle waqaf land is very important to be considered by institutions / individuals who are interested in PMDN investment in the agricultural sector and ziswaf management institutions. Every land and sea have the blessing and the competitive power of its own and its utilization as well as possible considering the state of the local community as a major source of labor, without neglecting the environmentaspartof sustainabledevelopment goals.Asmart-small- microinanc can be synergized with ziswaf as a step to strengthen the technical and managerial mustahik. Cash waqf can also be used as an instrument for the development of further capital. Economic growth is accompanied by sustainability is the best choice, the chance alignment of a sustainable Islamic inancial investment can be expanded globally in scope and impact. Islamic inancial transactions can be retained should provide investment categories permitted by religion (halal) and did well to supply logistics either through A-PLS or sukuk using the inancing agreements like salam, muzara'ah, and mugharasah; irrigation infrastructure for areas prone to lack of water with Musaqa or Istishna inancing. Careful handling prior to harvest, post - harvest handling of agricultural products and halal food processing industry is part of the growing Islamic Bankings sustainable advantage.